Neonatal and infantile appendicitis still confuses minds: report of two cases - Mustafa Okumuş; Adil Umut Zübarioğlu (SpringerOpen, 2020)
Abstract Background Acute appendicitis is extremely rare in the neonatal and infantile periods. The number of cases published in the last century is just over 100. Mortality and morbidity are still high due to diagnostic problems because there are no specific clinical features and reliable investigation for the diagnosis. Herein, we present two patients to remind physicians that the diagnosis of neonatal and infantile appendicitis should always be kept in mind. Case presentations A 30 3/7-week-old 740-g newborn girl was delivered by cesarean section because of preeclampsia. The newborn was followed in the neonatal intensive care unit and fed with an orogastric catheter. An abdominal distention developed on the 18th day of her life. While following up with a preliminary diagnosis of necrotizing enterocolitis, she was operated on the 4th day due to abdominal free air seen on X-ray. A perforated appendicitis was detected in the abdominal exploration and formal appendectomy was performed. Histology demonstrated marked transmural inflammation and necrosis at the perforated site and there was no evidence of Hirchsprung's disease. The patient was started on breast milk on the third postoperative day and discharged home on day 98. A 3.5-month-old boy was admitted to our clinic because of abdominal distention, discomfort, and constipation which had been ongoing for 4 days. He was followed up as an outpatient basis for 4 days in another center with the diagnosis of infantile colic. An increase in echogenicity due to intense inflammation was observed in mesenteric plans using USG in the right lower quadrant of the abdomen. Following preoperative preparations, the patient underwent abdominal exploration and appendectomy. He had an uneventful recovery and pathologic examination demonstrated a necrotizing appendicitis with perforation. He was discharged on the fourth postoperative day without any problems. Conclusion It is a fact that acute appendicitis in neonates and infants may not be diagnosed easily and quickly as in older children because there are no specific clinical features and reliable investigation for the diagnosis. Delay in diagnosis and treatment often results in appendicular perforation and peritonitis. The main safeguard against mortality and morbidity remains a high index of suspicion.